Peningkatan Kreativitas Anak Usia Dini Melalui Cerita Bergambar Pada Anak Didik Kelompok B RA Barokatussoulatiah NW Puyung - Harjanty, Rokyal; Fitriani, Laily (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
Children's creativity needs to be increased; therefore, learning must be interesting and fun. One way to increase creativity is through illustrated stories. This research aims to determine the increase in children's creativity through picture stories. This research is classroom action research. The subjects in this Creativity research were students from group B RA Barakatussoulatiyah NW Puyung. The number of students in group B RA Barakatussoulatiyah NW Puyung is 30 children. This research is collaborative between researchers, school principals, and accompanying class teachers. Data was collected through observation, field notes, interviews and documentation. The validity of the data was checked by triangulation. Data were analyzed using descriptive qualitative flow model. The results of this research show that there is an increase in children's creativity through picture stories, namely pre-cycle creativity of 13.33%, cycle I creativity of 46.67% and cycle II creativity of 80.00%. Increasing children's creativity through picture stories is also supported by several indicators, namely creative reactions, long attention spans, self-organization / self-confidence, linking ideas or ideas / telling stories, developing imagination and adding new vocabulary. Apart from that, success in increasing creativity is also supported by supporting methods, including providing time to explore and providing very good motivation. The conclusion of this research is that picture stories can increase children's creativity.